2020
DOI: 10.1101/2020.10.29.361139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pseudomonas aeruginosaandCandida albicansboth accumulate greater biomass in dual species biofilms under flow

Abstract: Spatially structured communities of microbes - biofilms - are widespread in nature, and biofilm-dwelling microbes often respond to their environments in ways that are different from their planktonic counterparts. Further, most natural biofilms are multi-species mixtures of microorganisms; the ecology of intra- and inter-species interactions in these consortia, and the resulting effects on total community properties, are often not well understood. A common site of polymicrobial biofilm infections is the lungs o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 100 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…10 The bacterium, Pseudomonas aeruginosa (Pa), and the polymorphic fungus, Candida albicans (Ca), are commonly found together. 11 Studies have shown that both physical contact and intercellular signalling by diffusible factors contribute to the interactions and behaviors of these bacteria-yeast communities. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…10 The bacterium, Pseudomonas aeruginosa (Pa), and the polymorphic fungus, Candida albicans (Ca), are commonly found together. 11 Studies have shown that both physical contact and intercellular signalling by diffusible factors contribute to the interactions and behaviors of these bacteria-yeast communities. Fig.…”
Section: Introductionmentioning
confidence: 99%